De quelle intégration s’agit-il? Immigration : de l’altérité à la lutte pour la reconnaissance - Baccouche, Nasser (Canadian Journal of Counselling and Psychotherapy, 2007)
Integration is a complex phenomenon which embraces all aspects of individual and social existence. It implies uprooting from exclusive belonging, knowing that contact between cultures necessarily alters their integrity thus leading to newly composed identities. That means a fixed definition based on an essentialized origin is an illusion because the unique trajectories of the social actors evolving in the spaces where they meet are subject to constant remodelling, unless self-ghettoization occurs. However, building an anthroposocial vision is fundamental to understanding the new social and identity compositions at work in the social fabric and recognizing them as plural public practices, thus legitimate and meaningful at the very heart of the city not as appendices that can be added or removed according to the interests of the moment. The issue is to establish a balance between the unique efforts by which the actors assert themselves as subjects combining specific characteristics and universal values. As can be seen in the case of Mx, that implies skill development to accept inner differentiation, to face tensions and conflicts, and to escape assigned roles and status in order to reclaim both equality and differences.